Exploring Needs in English Learning Materials for Visual Communication Design Students and Graduates: A Mixed-Methods Approach - Wijayanto, Pikir Wisnu; Barlian, Yelly Andriani; Nurbani, Sri (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2023)
The field of Visual Communication Design (VCD) in Indonesia requires students and graduates to enhance their English language skills to stay competitive globally. However, there is a significant gap in understanding the specific English language material needs of students and graduates in this field, so it needs to be more understanding of their particular linguistic needs. This mixed-methods study aims to explore the disparities in English language skills perceived by VCD students and graduates in Indonesia and identify their specific English language material needs. . Through questionnaires, interviews, and focus group discussions, data were collected from 30 students and 10 graduates. The findings reveal differences in language proficiency or skills perspectives between VCD students and graduates , emphasizing the importance of designing language courses that align with learners' specific needs and industry demands. This study's implications for English language education in various industries highlight the significance of effective communication in a globalized world. By addressing learners' specific language demands, educators can better support students' language learning goals and prepare graduates for success in their professional endeavors. Implementing industry-specific language instruction and curriculum can enhance learners' competitiveness and communication in the workplace, promoting stronger international collaborations within the creative industries. Although challenges may arise in implementing changes, a partnership between academic institutions and industry stakeholders can bridge the gap between academic language learning and real-world language demands. Addressing learners' needs in English language education can ultimately contribute to their professional growth and success in the global market.